Proceso de optimización de una estación base celular de tecnología GSM ubicada en la población de los Mineros en la provincia de Santo Domingo de los Tsáchilas - Enríquez Jaramillo, Fabián Esteban (2011)
This thesis develops the study of the optimization process of a wireless base station of GSM technology located in the Town of Miners in the province of Santo Domingo de los Tsáchilas to cover and benefit the community with cellular communication.